Faktor Risiko Terjadinya Karies Baru Pada Anak Sekolah Berdasarkan Pengukuran Dengan Cariogram - Quroti A’yun; Julita Hendrartini; Al Supartinah (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2016)
Caries risk factors were factors related to caries incidence in individu or population. Caries risk factors were different between individu. For illustrating the interaction between caries related factors may be used Cariogram. This research aimed to get the general overview of the order of caries risk factor in elementary school students in the distric of Sleman. The study was observational cross-sectional design. The sample was 76 children aged 10-12 years. New caries risk factors measured were caries experience, affecting disease, frequency of eating, the amount of plaque, Streptococcus mutans measurement, fluorine program, the secretion of saliva, buffer capacity, and clinical assessment. Results were analyzed with the software of Cariogram. The study showed that 63% of children was caries, 100% did not have a systemic disease, 53% of children had cariogenic food frequency with maximum of 3 times, 70% had plaque index of 0.04 to 1.0, measuring 47% of children have adhesion colony Streptococcus mutants 1-10, 100% brushing teeth with fluor toothpaste, 44% of children had secretion of 0.9-1.1 ml/mn, and 100% of children with a buffer capacity of saliva pH > 6. Cariogram measurement results showed the average percentage of vulnerability factors: 14% , meal pattern : 9%, bacteria : 5%, and suspect teeth and others factors: 3%. It can be concluded that the sequence of the risk factors in children from Cariogram measurement are vulnerability factors, meal pattern, bacteria, suspect teeth, and others factors.